Relative hypercoagulation induced by suppressed fibrinolysis after tisagenlecleucel infusion in malignant lymphoma - Yamasaki-Morita, Makiko; Arai, Yasuyuki; Ishihara, Takashi; Onishi, Tomoko; Shimo, Hanako; Nakanishi, Kayoko; Nishiyama, Yukiko; Jo, Tomoyasu; Hiramatsu, Hidefumi; Mitsuyoshi, Takaya; Mizumoto, Chisaki; Kanda, Junya; et al. (Blood advances, 2022)
Anti-CD19 chimeric antigen receptor T (CAR-T) cell therapy has facilitated progress in treatment of refractory/relapsed diffuse large B-cell lymphoma (DLBCL). A well-known adverse event after CAR-T therapy is cytokine release syndrome(CRS). However, the etiology and pathophysiology of CRS-related coagulopathy remain unknown. Therefore, we conducted a prospective cohort study to comprehensively analyze coagulation/ fibrinolysis parameters present in peripheral blood of adult DLBCL patients treated with tisagenlecleucel in a single institution. Samples were collected from 25 patients at 3 time points: before lymphocyte-depletion chemotherapy and on days 3 and 13 after CAR-T infusion. After infusion, all patients except 1 experienced CRS, and 13 required the administration of tocilizumab. A significant elevation in the plasma level of total plasminogen activator inhibitor 1 (PAI-1), which promotes the initial step of coagulopathy (mean, 22.5 ng/mL before lymphocyte-depletion and 41.0 on day 3, P = .02), was observed at the onset of CRS. Moreover, this suppressed fibrinolysis-induced relatively hypercoagulable state was gradually resolved after CRS remission with normalization of total PAI-1 to preinfusion levels without any organ damage (mean values of soluble fibrin: 3.16 µg/mL at baseline, 8.04 on day 3, and 9.16 on day 13, P < .01; and mean PAI-1: 25.1 ng/mL on day 13). In conclusion, a hypofibrinolytic and relatively hypercoagulable state concomitant with significant total PAI-1 elevation was observed at the onset of CRS even in DLBCL patients with mild CRS. Our results will facilitate understanding of CRS-related coagulopathy, and they emphasize the importance of monitoring sequential coagulation/fibrinolysis parameters during CAR-T therapy. •A hypofibrinolytic state with total PAI-1 elevation at the onset of CRS is the initial step of coagulopathy early after CAR-T infusion.•Suppressed fibrinolysis induces hypercoagulable status, which is gradually resolved after CRS remission without any organ damage in DLBCL. [Display omitted]